Conflicts Encountered with Bridge Team from the Perspective of Vessel Traffic Service Operators: A Research Within E-Navigation Concept - Arslan, Elif; Nas, Selçuk (Transactions on Maritime Science, 2022)
The hazards that threaten marine navigation safety in the intensive routes and critical straits need to be managed effectively. To manage these risks, the concept of e-navigation has been offered to all stakeholders of marine transportation. E-navigation basically aims to organize, serve, and exchange marine information systematically. It is considered that the relations between the stakeholders may constitute significant conflicts in exchanging marine information. The main purpose of this study is to reveal the sources of conflicts and risk scores on navigation operations encountered with the bridge team from the perspective of vessel traffic services operators (VTSOs). In order to determine the sources of the conflicts, the conflict-related literature has been thoroughly reviewed, a semi-structured interview form was developed, and the VTS supervisors have been interviewed. In discovering the sources of conflicts, content analysis has been carried out from the interviews. The findings have been discussed with the relevant experts, and risk scales have been developed to evaluate the risks of conflicts. The frequency of conflicts and the results have been evaluated by the VTSOs employed at the Center of VTS in İstanbul, and risk scores have been defined. The risk scores related to the conflicts indicated on the risk matrix and e-navigation designed solutions have been compared and discussed. The findings reveal that there are certain similarities between the high-scored risks regarding communication quality and reporting systems. Although e-navigation solutions focus on improving technical issues. Conflicts caused by interpersonal, cognitive, and personal features that are not covered by e-navigation solutions have an important place among the conflict sources.